Realigning reverse e-auctions for organisational magility. - Tassabehji, Rana (2009)
No === With the advent and maturity of the internet, reverse electronic auctions (e-auctions) are now an important mechanism for public and private sector organisations, in the procurement of goods and services. Here, a novel link is made between reverse electronic auctions (e-auctions) and its potential impact on organisational agility, a link not previously developed in the literature. In this paper, we justify this relationship from a theoretical perspective. We investigate how information and internet technology impacts procurement, by an analysis and evaluation of the literature. E-auctions are reviewed and organisational agility defined; the advantages of agile management are also identified and the role that e-auctions can play in achieving this, discussed. Strategies for re-aligning reverse e-auctions in support of organisational agility are proposed and the advantages of this process discussed. Recommendations for future practice that will maximise the chances of realising agile systems management are also presented. Finally, areas for further research are identified.